Differential Effects of Toluene and Ethanol on Dopaminergic Neurons of the Ventral Tegmental Area - Nimitvilai, Sudarat; You, Chang; Arora, Devinder S.; McElvain, Maureen A.; Vandegrift, Bertha J.; Brodie, Mark S.; Woodward, John J. (Frontiers in Neuroscience, 2016)
Drugs of abuse increase the activity of dopaminergic neurons of the ventral tegmental area (VTA), and output from the VTA is critical for both natural and drug-induced reward and reinforcement. Ethanol and the abused inhalant toluene both enhance VTA neuronal firing, but the mechanisms of this effect is not fully known. In this study, we used extracellular recordings to compare the actions of toluene and ethanol on DA VTA neurons. Both ethanol and toluene increased the firing rate of DA neurons, although toluene was ~100 times more potent than ethanol. The mixed ion channel blocker quinine (100 μM) blocked the increases in firing produced by ethanol and toluene, indicating some similarity in mechanisms of excitation. A mixture of antagonists of GABA and cholinergic receptors did not prevent toluene-induced or ethanol-induced excitation, and toluene-induced excitation was not altered by co-administration of ethanol, suggesting independent mechanisms of excitation for ethanol and toluene. Concurrent blockade of NMDA, AMPA, and metabotropic glutamate receptors enhanced the excitatory effect of toluene while having no significant effect on ethanol excitation. Nicotine increased firing of DA VTA neurons, and this was blocked by the nicotinic antagonist mecamylamine (1 μM). Mecamylamine did not alter ethanol or toluene excitation of firing but the muscarinic antagonist atropine (5 μM) or a combination of GABA antagonists (bicuculline and CGP35348, 10 μM each) reduced toluene-induced excitation without affecting ethanol excitation. The Ih current blocker ZD7288 abolished the excitatory effect of toluene but unlike the block of ethanol excitation, the effect of ZD7288 was not reversed by the GIRK channel blocker barium, but was reversed by GABA antagonists. These results demonstrate that the excitatory effects of ethanol and toluene have some similarity, such as block by quinine and ZD7288, but also indicate that there are important differences between these two drugs in their modulation by glutamatergic, cholinergic, and GABAergic receptors. These findings provide important information regarding the actions of abused inhalants on central reward pathways, and suggest that regulation of the activation of central dopamine pathways by ethanol and toluene partially overlap.